2018
DOI: 10.1159/000495157
|View full text |Cite|
|
Sign up to set email alerts
|

Galectin-1 Promotes Metastasis in Gastric Cancer Through a Sphingosine-1-Phosphate Receptor 1-Dependent Mechanism

Abstract: Background/Aims: Increased expression of galectin-1 (Gal-1) in gastric cancer (GC) promotes metastasis and correlates with poor prognosis. The mechanisms by which Gal-1 promotes GC metastasis remain unknown. Methods: Gal-1and Sphingosine-1-phosphate receptor 1 (S1PR1) were determined by immunohistochemistry(IHC) and quantitative real time polymerase chain reaction (qRT-PCR) in GC specimens. Stably transfected Gal-1 or S1PR1 into SGC7901 and MGC-803 cells, western blot and invasion assays in vitro and nude mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…5 B, C), suggesting that PRRX1 may promote tumor malignancy by suppressing PKA signaling in human osteosarcoma. Furthermore, our RNA transcriptome data also revealed that PRRX1 knockdown decreased the expression level of S1PR1 that has been reported to be a critical molecule for metastasis [45] , [46] , [47] . Althogh we did not assessed the functional relationship between S1PR1 and PRRX1 in this study, this may be a critical factor to cause the malignancy of osteosarcoma.…”
Section: Discussionsupporting
confidence: 53%
“…5 B, C), suggesting that PRRX1 may promote tumor malignancy by suppressing PKA signaling in human osteosarcoma. Furthermore, our RNA transcriptome data also revealed that PRRX1 knockdown decreased the expression level of S1PR1 that has been reported to be a critical molecule for metastasis [45] , [46] , [47] . Althogh we did not assessed the functional relationship between S1PR1 and PRRX1 in this study, this may be a critical factor to cause the malignancy of osteosarcoma.…”
Section: Discussionsupporting
confidence: 53%
“…Gal-1 is a cell-autocrined protein, which plays an important role in the development and metastasis of many tumors [14]. Some studies have confirmed that Gal-1 is specifically expressed in many tumor tissues and regulates various biological activities of cancer cells, such as breast cancer, gastric cancer [15,16]. However, Gal1 has little research on the role of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…It interacts with oncogenic H-Ras and promotes cell migration, demonstrating its key role in driving tumor transforming proteins to affect tumor progression, invasion, and angiogenesis (12,13). A large number of studies have suggested that galectin-1 is amplified and highly expressed in thyroid cancer, head and neck cancer, gastric cancer, colon cancer, ovarian cancer, and prostate cancer (14)(15)(16), and the high expression of galectin-1 is correlated with poor prognosis (17)(18)(19). However, few studies have evaluated the relationship between galectin-1 expression and the survival rate of patients with rectal cancer.…”
Section: Discussionmentioning
confidence: 99%